A Study of Learning Resource Needs for International Students Majoring in "Chinese and Forestry" Based on the KANO Model: 基于KANO模型的“中文+林学”专业来华留学生学习资源需求研究 - Shuai Shao (Mandarinable: Journal of Chinese Studies, 2026)
With the development of International Chinese Language Education, the scale of Chinese learners has been expanding, and their learning needs have extended to various professional fields, leading to a growing number of studies on “Chinese + Major”. However, there are few researches from the perspective of students, especially in specific fields such as “Chinese + Forestry”. This study focuses on learners majoring in “Chinese + Forestry” and makes an in-depth investigation into the needs of such a student group in terms of learning resources. Firstly, a needs framework is established, covering 18 items in 5 categories. Then, a Kano-based questionnaire survey is conducted among 60 such students at Zhejiang A&F University. The results show that 3 resources (including professional course resources and campus environment) are essential and must be satisfied, 4 resources (including academic research resources, and laboratories and training bases) are desired and should be provided with priority, 6 resources (including personalized learning plans, employment and career development, and cultural exchange experience) are attractive and need to be focused on, and 5 resources (including language proficiency assessment, college selection guidance and social network construction) are indifferent and need attention to the changes in the needs for them at any time. The research provides basic data and teaching enlightenment for the construction of learning resource needs of international students majoring in “Chinese + Forestry” and any other “Chinese + Major”.